Analysis Of Tax Compliance Based On Psychological Factors And Tax Administration - Baeli, Jonathan (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2021)
Awareness of paying taxes is a personal area that is abstract and difficult to measure. However, it can still be pursued by taking into account the factors that influence it, including financial condition and awareness of paying taxes, as well as presenting professional and pleasant tax services. This research is part of the survey method, in which research data is obtained through distributing questionnaires to 100 respondents. The sampling technique adheres to incidental assumptions. The results of the study state that awareness of paying taxes will increase when various conditions are met, including the implementation of easy tax services, the existence of a penalty system for delays (in the form of population administration sanctions), a high desire to contribute to the state (nationalism motivation), and the financial condition of taxpayers. It is firmly estimated at 95%. This means that there will be an increase in participation in paying taxes by 95% of the total taxpayers. This is very helpful for government revenue receipts.